Dietary Habits and Lifestyle During Coronavirus Pandemic Lockdown: Experience From Lebanon - Cheikh Ismail, Leila; Hashim, Mona; Mohamad, Maysm N.; Hassan, Hussein; Ajab, Abir; Stojanovska, Lily; Jarrar, Amjad H.; Hasan, Hayder; Abu Jamous, Dima O.; Saleh, Sheima T.; Al Daour, Rameez; Osaili, Tareq M.; et al. (Frontiers in Nutrition, 2021)
This study aimed to examine the impact of quarantine on eating habits and lifestyle behaviors among the Lebanese adult population. A cross-sectional study was conducted using an online questionnaire designed on Google Forms between 3 June and 28 June 2020. The survey questions were adapted from the Short Food Frequency Questionnaire, the International Physical Activity Questionnaire Short Form, and the second version of the Copenhagen Psychosocial Questionnaire. A total of 2,507 adults completed the questionnaire. During the lockdown, 32.8% claimed weight gain, 44.7% did not eat fruits daily, 35.3% did not eat vegetables on daily basis, and 72.9% reported drinking less than eight cups of water per day. Moreover, there was a significant increase in the number of meals consumed per day, consumption of homemade meals, sedentary time, stress, and sleeping disturbances during the pandemic compared to before the pandemic (all p < 0.001). However, there was a significant decrease in physical activity engagement, sleep quality, and energy level during the lockdown compared to before the pandemic (all p < 0.001). The study highlights that the COVID-19 lockdown was associated with unfavorable changes in dietary habits and lifestyle behaviors in Lebanon. Sleep and mental health were also negatively impacted by the pandemic.